Analysis of high frequency Alfvén eigenmodes observed in ASDEX Upgrade plasmas in the presence of RF-accelerated NBI ions. (14th February 2023) - Ochoukov, R.; Sipilä, S.; Bilato, R.; Bobkov, V.; Dreval, M.; Weiland, M.; Dendy, R.; Faugel, H.; Johnson, T.; Kappatou, A.; Kazakov, Y.; McClements, K.G.; et al.
Abstract: High frequency Alfvén eigenmodes in the ion cyclotron frequency range are actively researched on the ASDEX Upgrade tokamak (AUG). The general properties of this particular mode type are: ( a ) the mode is beam-driven and, if excited, can persist for the entire duration of the beam-on time window; ( b ) the mode is sub-cyclotron with the frequency ω ∼0.5 ω ci, where ωci corresponds to the on-axis cyclotron frequency of the beam ions; ( c ) the mode propagates in the counter-current/counter-injection direction; and ( d ) the field-aligned (∼toroidal) mode number is large: | n // | ∼50. It has been observed on AUG that radio frequency- (RF)-acceleration of beam-injected ions at the 3rd cyclotron harmonic significantly expands the number of excited modes. In this work we demonstrate how this observation is consistent with the global Alfvén eigenmode (GAE) behavior. The RF-driven fast ion population is modeled using a combination of an orbit-following Monte Carlo code (ASCOT-RFOF) and an electro-magnetic wave code (TORIC). The application of this code combination is a first to model beam-ion RF-acceleration at the 3rd cyclotron harmonic. The RF-accelerated fast ion distributions are then used to analytically calculate anisotropy-driven mode growth rates. We see that the region of positive (unstable) growth rates is expanded by RF-accelerated fast ions in both the frequency and the mode number directions for the GAEs, consistent with the measurements. Although the compressional Alfvén eigenmode growth rates are also positive for our particular fast ion distributions, the growth rate values are ∼3 orders of magnitude lower. The plasma conditions on AUG are more destabilizing to the GAEs. Overall, our results are consistent with the observation of similar modes on other conventional tokamaks, namely JT-60U and DIII-D.